Duplication of Serial Set publications in the American State Papers: an annotated inventory - Imholtz, August A., author; Draper, Daniel C., author; American Library Association, publisher (Colorado State University. Libraries, 2013)
The American State Papers collection of Congressional and Executive Branch publications, which in total number more than 6,300 documents, not only covers the fourteen Congresses before the initiation of the Congressional Serial Set in Dec. 1817 but for the final three-fifths of the collection overlaps chronologically with the first two decades of the Serial Set. Over 2,650 of the American State Papers publications reprint, with some occasional minor alterations and a few major ones, Reports and Documents originally published in the Serial Set. This paper provides for the first time an annotated list of all those duplicated publications.
Article and Appendixes: Foreign Relations, Indian Affairs, Commerce & Navigation, Post Office, and Miscellaneous tables.
Keywords: United States congressional serial set; American state papers